1995
DOI: 10.1017/s0016756800021506
|View full text |Cite
|
Sign up to set email alerts
|

The first record ofCooksoniafrom South Americain Silurian rocks of Bolivia

Abstract: Plant megafossils resembling Cooksonia caledonica Lang are described from the Kirusillas Formation in southern Bolivia. Faunal and lithological evidence together with field relationships advocate a late Silurian (Ludlow) age. Palaeocontinental reconstructions suggest that the plants grew on the western edge of Gondwana at 50-60° S and indicate that Cooksonia had spread to higher latitudes soon after its appearance in the Wenlock.Branching is isotomous. Between bifurcations the naked axes are parallel-sided whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Such a conclusion has major phytogeographic implications indicating the presence of a possible Lochkovian Laurussian species at high latitudes (c. 60°C) in the uppermost Silurian of Gondwana (Morel et al, 1995) (Fig. 81).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Such a conclusion has major phytogeographic implications indicating the presence of a possible Lochkovian Laurussian species at high latitudes (c. 60°C) in the uppermost Silurian of Gondwana (Morel et al, 1995) (Fig. 81).…”
Section: Discussionmentioning
confidence: 90%
“…Olive-green, finely micaceous rusty weathering silty mudstones, siltstones and fine sandstones dip consistently to the south at 70"-80". This is the sequence from where Petriella & Suarez Soruco (1989) first reported plants, and Morel et al (1995) identified the fertile specimen of Cooksonia.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The most comprehensive reports have been from the Middle and Upper Devonian of western Venezuela (Berry, Edwards and co-authors) and the Silurian/Lower Devonian of Bolivia/Argentina (Morel, Edwards & Iñigez Rodriguez, 1995). This scarcity of fossil evidence has frustrated attempts at global phytogeography during these times (Edwards & Berry, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These were ®rst noted by Petriella and Sua Ârez Soruco (1989). Morel et al (1995) described the ®rst South American record of Cooksonia from the Kirusillas Formation of Negra Muerte near Tarija. Possible algal or other plant remains occur together with the graptolites at Cerro Sikimirani Jatun (locality 4 herein), which have not been recognised previously.…”
mentioning
confidence: 99%